Ath-thoriqah ahammu minal madah dalam Perspektif KH. Hasyim Asy’ari dan Operasionalisasi dalam Pembelajaran di STIT Raden Wijaya Mojokerto - Achmad Padi (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
The problem of education in this country, in addition to the curriculum, methods are also in the spotlight. This can be understood because the method is indeed more important than the curriculum, you know that your knowledge is good. But the method also depends on the implementation of the teacher, because the teacher is more important than the method itself, al-mudarris ahammu min ath thariqah. However, the spirit of a teacher is more meaningful than his own body, wa ruhul mudarris ahammu min mudarris nafsuhu. Because of any sophisticated method, if you are in a teacher who is not eager to have nothing. The principle of the interrelationship between curriculum, methods, and teachers, has been recognized by the importance of Hasyim Asy'ari and the muktabar scholars who are directly involved in the care of educational institutions. The purpose of this study is to describe Ath-thoriqah your understanding is in the perspective of KH. Hasyim Asy'ari and Operationalization in Learning at STIT Raden Wijaya Mojokerto. 1) Education offered by KH. Hasyim Asy'ari is a character-based education that is being heralded by the current Minister of Education to be used as a reference in the formation of character of students. 2) In the process of improving teaching, Ath-thoriqah will understand. Or At-thorikotu ahammu minal maddah wal mudarisu ahammu interest in tharikoh wa ruhul mudaris ahammu minal mudarris as conveyed by Kyai Dr. H. Syukri Zarkasyi, MA, needs to be sustained by the Soul of a Teacher and not limited to the capacity of his own teacher who is still reluctant in his heart